Phthalocyanine-pyrene conjugates: A powerful approach toward carbon nanotube solar cells - Bartelmeß, Jürgen; Ballesteros, Beatriz; De La Torre, Gema; Kießling, Daniel; Campidelli, Stephane; Prato, Maurizio; Torres, Tomas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2010)
In the present work, a new family of pyrene (Py)-substituted phthalocyanines (Pcs), i.e., ZnPc-Py and H Pc-Py, were designed, synthesized, and probed in light of their spectroscopic properties as well as their interactions with single-wall carbon nanotubes (SWNTs). The pyrene units provide the means for non-covalent functionalization of SWNTs via π-π interactions. Such a versatile approach ensures that the electronic properties of SWNTs are not impacted by the chemical modification of the carbon skeleton. The characterization of ZnPc-Py/SWNT and H Pc-Py/SWNT has been performed in suspension and in thin films by means of different spectroscopic and photoelectrochemical techniques. Transient absorption experiments reveal photoinduced electron transfer between the photoactive components. ZnPc-Py/SWNT and H Pc-Py/SWNT have been integrated into photoactive electrodes, revealing stable and reproducible photocurrents with monochromatic internal photoconversion efficiency values for H Pc-Py/SWNT as large as 15 and 23% without and with an applied bias of +0.1 V. © 2010 American Chemical Society.